Optical design of LED high mast lamp based on TIR freeform lens for annular lighting. (October 2021) - Pan, D; Zhang, YC; Xie, XF; Fan, MJ; Chen, YA; Yan, SH; Yang, SJ
The traditional square spot of street lamp is not suitable for the lighting requirements of the annular road lighting. In this paper, a lens design method for producing annular spot of high mast lamp is proposed. The method mainly contains three optical surfaces, in which the inner surface collimates the energy of the centre part of the light source, the total internal reflection surface collimates the light with large angle and low energy and the outer surface refracts all the collimated light to realise the annular illumination distribution on the target surface. In this design, we can change the diameter of the lighting spot through the variation of the inclination angle of the outer surface from 14° to 19° and the diameter of the spot changes from 10.2 m to 12.3 m at the distance of 30 m. The lighting requirements of high mast lighting are realised based on the TIR lens array, in which the average illuminance is more than 20 lx, the illuminance uniformity is more than 0.7 and the light optical utilisation factor is more than 90%.